Factors influencing outcomes in clinical transplantation 1 - Wood, Kathryn (Henry Stewart Talks, 2021)
Clinical transplantation, Immunosuppressive drugs, Long-term graft survival, Immune responses to transplants, Rejection, Alloantibodies, Antibody-mediated rejection (AMR), Hyperacute rejection, Technology available for detecting and specifying HLA and non-HLA antibodies, B cells and transplant rejection